Relationship Between Coffe Steam Prototype Innovation and Coffe Farmers Cikoro Village Gowa Regency - Sri Kartina; Andi Tenry Sose; Darmawati Manda; Ismail Ismail; Henni Zainal (Pinisi Business Administration Review, 2021)
Temperature greatly affects the drying process of coffee, while the village of Cikoro is one of the cold-temperature areas. to produce a hot temperature before the community had tried oven techniques but it was less successful, so the alternative used so far was to do drying in Makassar. In the study that became participants were coffee farmers in Cikoro. The purpose of the studies we conducted clearly provided solutions to the community for the problems experienced. To understand and resolve this problem we use the desigen thinking method that focuses on users or users with several stages, namely sense and sensitivity, empathy study, collecting data, clustering, insight, statement, persona, ideation, prototype, and co-coreation then obtained more accurate data so as to create an innovation in the form of a prototype coffee drying machine (Coffee Steam) as a solution for coffee farmers in Cikoro. The purpose of this study was to determine the response of the community in accepting the innovation of coffee steam prototype.